The perception of primiparous mothers of comfortable resources in labor pain (a qualitative study) - Tahereh Boryri; Noor Mohammad Noori; Alireza Teimouri; Fariba Yaghobinia (Wolters Kluwer Medknow Publications, 2016)
Background: Natural delivery is the most painful event that women experience in their lifetime. That is why labor pain relief has long been as one of the most important issues in the field of midwifery. Thus, the present study aims to explore the perception of primiparous mothers on comfortable resources for labor pain. Materials and Methods: In the present study, qualitative content analysis technique was used. The participants had singleton pregnancy with normal vaginal delivery. These women referred to the Imam Javad Health Center within 3-5 days after delivery for screening thyroid of their babies. Results: During the content analysis process, five themes emerged that indicated the nature and dimensions of the primiparous mothers' perception of comfortable resources. These themes were: "religious and spiritual beliefs," "use of analgesic methods" (medicinal and non-medicinal), "support and the continuous attendance of midwife and delivery room personnel," "family's and husband's support during pregnancy and in vaginal delivery encouragement," and finally "lack of familiarity with the delivery room and lack of awareness about structured delivery process." Conclusions: The results showed that mothers received more comfort from human resources than from the environment and modern equipment. Despite the need for specialized midwife with modern technical facilities, this issue shows the importance of highlighting the role of midwife and humanistic midwife care. Therefore, considering midwives and the standardization of human resources in health centers are more important than physical standardization. This will result in midwife interventions being performed with real understanding of the patients' needs.